Latent code manipulation for text-to-image and video synthesis: evaluating generative networks - Masiya, Elvis (Stellenbosch : Stellenbosch University, 2025)
Masiya, E. 2025. Latent Code Manipulation for Text-to-Image and Video Synthesis: Evaluating Generative Networks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/c8269505-2925-45f9-bb22-359d6ac30e7a